Diversidade taxonômica e funcional de formigas da diagonal seca - Mariáh Leite Tibcherani (2022)
Biogeography understands the patterns of species distribution and geographic variation in composition through biotic and abiotic mechanisms and processes that may be involved, resulting in information on how changing environmental factors influence the current distribution of species. Thus, considering the variation of environmental factors in South America, the dry diagonal, formed by the Caatinga, Cerrado and Chaco, is characterized by periods of severe drought. In this way, ants can be used in biogeographic studies since they are well distributed throughout the globe, not being found only at the poles, evidencing that they are adapted to wide variations in temperature and humidity. Thus, the first chapter aims to verify the influence of evolutionary history on the richness, composition, and taxonomic diversity of ants from the Caatinga, Cerrado and Chaco, comparing alpha, beta and gamma diversity. The second chapter aims to evaluate the functionality of the ant community in each of the dry diagonal domains and between them, in addition to verifying the functional richness, functional dispersion and functional redundancy of each of the domains and establishing the functional groups of ants from the Caatinga, Cerrado and Chaco.